Using ICT Tools for Exploring the Impact of Urban Blue-Green Spaces on Human Health and Well-Being - Sanja IVANKOVIC; Dragana JOVANOVIC; Predrag SAVIC; Vesna KARADŽIĆ; Milena VASIĆ (Applied Medical Informatics)
Worldwide, public health and well-being are significantly impacted by disruptions in physical, biological, and ecological systems stemming from urban environmental burdens. The H2020 project, "Healthier Cities through Blue-Green Regenerative Technologies: the HEART Approach," employs an innovative systemic methodology that integrates water (blue) and vegetated areas (green) infrastructure to address these challenges. The primary methodological approach of HEART clinical studies across three demonstration cities focuses on understanding how HEART project interventions relate to four chronic disease groups: cardiovascular, respiratory, mental, and metabolic conditions, with healthy participants as the control group. HEART study is using ICT tools as instruments in studying how blue-green spaces (BGS) impact public health and well-being in urban areas. 800 volunteers are equipped with smart-bands during their active time at demo sites in the cities of Belgrade, Athens and Aarhus. These wearable devices enable collection of biometric data, and project oriented mobile applications developed in collaboration between IT and medical experts guide participants on BGS visits, potentially monitor other health-related data and facilitate digital collection of socio-economic-medical questionnaires. Data collected from clinical measurements, laboratory tests, wearable devices, environmental sensors, and socio-economic-medical questionnaires will be analyzed using AI tools and statistical methods. These methods help to identify patterns and correlations between BGS visits and health outcomes. Overall, these ICT tools and methods are integral to the HEART project, enabling comprehensive data collection, real-time monitoring, and advanced analysis to evaluate the impact of BGS on public health and well-being in urban environments.